1988
DOI: 10.1007/bf02552544
|View full text |Cite
|
Sign up to set email alerts
|

Experimental ileal J-pouch construction

Abstract: Endorectal ileal pouch-anal anastomosis has become the surgical alternative of choice for patients requiring colectomy for ulcerative colitis or familial polyposis coli. The optimal method of ileal pouch construction has not been determined. In this study, a canine preparation was used to compare the immediate results of three different techniques of ileal J-pouch construction. The three methods studied were two-layer hand-suturing (HS), stapling through enterotomies placed laterally on the ileal limbs (LS), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The following reaction of protonated/deuterated dichloroethylmethylsilane with zinc oxide [10][11][12] resulted in a mixture of cyclic protonated/deuterated (mainly EM3 and 2,4,6,8-tetraethyl-2, 4,6,8-tetramethylcyclotetrasiloxane) and oligomeric protonated/deuterated ethylmethylsiloxanes [reaction step (8)]. The zinc ions were precipitated with sodium carbonate to avoid polymerization during the following fractional distillation under reduced pressure, isolating the cyclotrisiloxane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following reaction of protonated/deuterated dichloroethylmethylsilane with zinc oxide [10][11][12] resulted in a mixture of cyclic protonated/deuterated (mainly EM3 and 2,4,6,8-tetraethyl-2, 4,6,8-tetramethylcyclotetrasiloxane) and oligomeric protonated/deuterated ethylmethylsiloxanes [reaction step (8)]. The zinc ions were precipitated with sodium carbonate to avoid polymerization during the following fractional distillation under reduced pressure, isolating the cyclotrisiloxane.…”
Section: Resultsmentioning
confidence: 99%
“…EM3 can be prepared by the condensation reaction of commercially available protonated dichloroethylmethylsilane with zinc oxide. This method has already been applied to symmetrically substituted dichlorodialkylsilanes [10], to dichlorodiphenylsilane [ 11 ], and to dichloromethylphenylsilane [ 12]. To our knowledge, no synthetic pathway of 2,4,6-tri(pentadeuteroethyl)-2,4,6-tri(trideuteromethyl)cyclotrisiloxane (hereafter called EMrd24) starting from perdeuterated ethanol and methanol exists in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the ring-opening polymerization of cis-D Ph 3 gave stereoregular poly(methylphenylsiloxane) (PMPS), which exhibited a small degree of crystallinity and slight dependence of T g on tacticity. 4,5 However, assignment of the triad signals of PMPS in 1 H NMR is not unambiguously established. Ballauff and co-workers 4 Bresler et al 9 and Llorente et al 13 suggested that the peak of syndiotactic triad should appear at higher ®eld than that of isotactic triad (I = 0.19, H = 0.14, S = 0.09 ppm), whereas a contra- dictory assignment was suggested by Baratova et al 7,8 (S = 0.13, H = 0.08, I = 0.03 ppm).…”
Section: ±3mentioning
confidence: 99%
“…Apparently, the effect of the stereoregularity on T g was not signi®cant, in contrast to the case of PMPS rich in isotacticity. 4,5 However, because T g also depends on the molecular weight together with the tacticity of the polymers, no concrete conclusion can be drawn. In addition, it seems necessary to prepare pure syndiotactic PMPS with high molecular weight to conclude studies on the effect of stereoregularity on the physical properties.…”
Section: Effect Of Stereoregularity On Physical Properties Of Pmpsmentioning
confidence: 99%